A Comparative Evaluation of MgSo4 and Dexamethasone as an Adjuvant to Local Anaestheticin Brachial Plexus Block (USG Guided) for Upper Limb Surgery - Patel, Kinjal B.; Patel, Dhruvini H.; Shah, Rupal B.; Panagar, Kunj R. (Academia Anesthesiologica International, 2022)
Background: The aim of this research was to evaluate the addition of MgSO4 beside dexamethasone to bupivacaine in the prolongation of ultrasound-guided supraclavicular brachial plexus block for uppet limb surgeries. Subjects and Methods: A total of 60 patients, ASA I and II grades, undergoing upper limb surgeries were registered in this research. The Ultrasound guided Supraclavicular brachial plexus block was performed with 0.5% bupivacaine 20 ml plus either 2 ml dexamethasone 8 mg (group D) or 2 ml of 10% MgSO4 (group M). The data collected were: the onset of sensory and motor block, the duration of sensory and motor block and the analgesic duration. Results: The onset of sensory and motor block, the duration of sensory and motor block and the time to first analgesic demand was significantly longer (P<0.05) in Group D. Intra-operative hemodynamics was analogous and no substantial side effect was observed in the research. Conclusion: Present research exhibits that the addition of Dexamethasone to Bupivacaine when compared to addition of MgSO4 to Bupivacain in supraclavicular brachial plexus block provides improved sensory and motor block duration and prolonged duration of analgesia with no side effects, therefore could be a additional balanced mixture.